أثر توجه المستهلك نحو المنتجات الخضراء على السلوك الشرائي -دراسة ميدانية على طلبة الجامعات الجزائرية - Ben Ahmed, Assia (Finance and Business Economies Review, 2018)
The aim of this study was to determine the effect of consumer attitude towards green products on purchasing behavior. The consumer attitude was measured by the following dimensions (individual responsibility, role of institutions and governments, financial role, knowledge of environmental issues), The study population represented by University of Sidi Bel Abbes, and the size of the sample was 300 students. The researcher used a questionnaire to collect the data and 263 questionnaires were retrieved. 245 questionnaires were valid for the analysis. The study reached a number of results, the most important of which are: the impact of environmental responsibility and the role of institutions and governments, and there was no effect of financial role and knowledge of environmental issues. Some recommendations were made, the most important of which was raising environmental awareness among students and encouraging them to buy green products